El Tor Biotype Vibrio cholerae Activates the Caspase-11-Independent Canonical Nlrp3 and Pyrin Inflammasomes - Mamantopoulos, Michail; Frising, Ulrika C.; Asaoka, Tomoko; van Loo, Geert; Lamkanfi, Mohamed; Wullaert, Andy (Frontiers in Immunology, 2019)
Vibrio cholerae is a Gram-negative enteropathogen causing potentially life-threatening cholera disease outbreaks, for which the World Health Organization currently registers 2–4 million cases and 100.000 cholera-associated deaths annually worldwide. Genomic Vibrio cholerae research revealed that the strains causing this ongoing cholera pandemic are members of the El Tor biotype, which fully replaced the Classical biotype that caused former cholera pandemics. While both of these biotypes express the characteristic Cholera Toxin (CT), the El Tor biotype additionally expresses the accessory toxins hemolysin (hlyA) and multifunctional auto-processing repeat-in-toxin (MARTX). Previous studies demonstrated that the Classical biotype of Vibrio cholerae triggers caspase-11-dependent non-canonical inflammasome activation in macrophages following CT-mediated cytosolic delivery of LPS. In contrast to the Classical biotype, we here show that El Tor Vibrio cholerae induces IL-1β maturation and secretion in a caspase-11- and CT-independent manner. Instead, we show that El Tor Vibrio cholerae engages the canonical Nlrp3 inflammasome for IL-1β secretion through its accessory hlyA toxin. We further reveal the capacity of this enteropathogen to engage the canonical Pyrin inflammasome as an accessory mechanism for IL-1β secretion in conditions when the pro-inflammatory hlyA-Nlrp3 axis is blocked. Thus, we show that the V. cholerae El Tor biotype does not trigger caspase-11 activation, but instead triggers parallel Nlrp3- and Pyrin-dependent pathways toward canonical inflammasome activation to induce IL-1β-mediated inflammatory responses. These findings further unravel the complex inflammasome activating mechanisms that can be triggered when macrophages face the full arsenal of El Tor Vibrio cholerae toxins, and as such increase our understanding of host-pathogen interactions in the context of the Vibrio cholerae biotype associated with the ongoing cholera pandemic.